Jacques le Juste, un Oblias parmi d'autres - Bourgel, Jonathan (New Testament studies, 2013)
In his Church History, Eusebius quotes a passage from Hegesippus's lost Memories in which he relates the martyrdom of James the Just; according to this account, the latter was called ᾽Ωβλίας. This article proposes to examine this odd term whose precise meaning remains obscure. Beyond issues related to its signification, the analysis of this word is likely to shed new light on the milieu in which the tradition quoted by Hegesippus appeared. This study seeks to demonstrate through various examples that the figure of the ᾽Ωβλίας was particularly popular in Jewish literature following the destruction of the Second Temple., French abstract: Au deuxième livre de son Histoire Ecclésiastique, Eusèbe de Césarée cite un récit du martyre de Jacques le Juste qu'il dit tenir des Mémoires d'Hégésippe. Ce texte rapporte notamment que Jacques était surnommé ᾽Ωβλίας. Le présent article propose d'examiner cet étrange terme dont le sens demeure controversé. Au-delà des questions relatives à sa signification, l'analyse de ce vocable est susceptible d'apporter un éclairage nouveau sur le milieu dans lequel apparut la tradition reproduite par Hégésippe. Cette étude cherche à démontrer à partir d'exemples divers, que le motif littéraire de l'᾽Ωβλίας fut particulièrement populaire dans la littérature juive de l'après-destruction du Second Temple.